2012
DOI: 10.1111/j.1754-7121.2012.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

The limits of learning: Policy evaluation and the Ontario Ministry of Research and Innovation

Abstract: This article reviews recent efforts by the Ontario Ministry of Research and Innovation (MRI) to measure and evaluate the success of its policies. It argues that these efforts have been inhibited by changes in the ministry's political context and the inherent complexity of the issues that innovation policies seek to address. The innovation strategy pursued by the ministry incorporates an element of mediated causality in its program logic, which complicates efforts to determine policy outcomes. When compounded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…To elucidate research use capacity in these diverse policy contexts, this paper investigates Canadian provincial governments, focusing on the fields of education (K‐12 and higher education) and science & technology. The former is a longstanding and well‐established provincial responsibility; the latter has been an area of increasing importance among the provinces since the 1980s (Friedman and Friedman ; Sá ; Sharaput ). The following question guided our inquiry: what capacity exists at the provincial level to access, generate, and use research in the policy process?…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate research use capacity in these diverse policy contexts, this paper investigates Canadian provincial governments, focusing on the fields of education (K‐12 and higher education) and science & technology. The former is a longstanding and well‐established provincial responsibility; the latter has been an area of increasing importance among the provinces since the 1980s (Friedman and Friedman ; Sá ; Sharaput ). The following question guided our inquiry: what capacity exists at the provincial level to access, generate, and use research in the policy process?…”
Section: Introductionmentioning
confidence: 99%
“…Energiesprong has been adapted in the Canadian context by a community in Alberta (Amerongen 2018). Canada also has institutions and innovation intermediaries in place to promote innovation and disruption (Sharaput 2012; Hepburn 2013; Jordaan et al 2017); these may be found in areas that cross over between technological and social innovation (Sud 2013; Ryerson University 2016; Centre for Social Innovation 2018; Climate Co‐Lab 2018). Additionally, there is a range of actors and networks already involved in building retrofits (Kennedy et al 2001; Parker and Rowlands 2007; Persram 2011; City of Toronto 2017; Hoicka and MacArthur 2018).…”
Section: Recommendationsmentioning
confidence: 99%
“…Canadian federalism is part of the problem. Research by Mitchell and Ledwell (2011), Creutzberg (2011), and Sharaput (2012), among others, has emphasized the need for a clearer division of policy roles among the federal and provincial governments in Canada to support innovation. The federal government has an overall responsibility for Canada’s economic competitiveness and social well-being, yet the higher education sector, including its universities, is regulated and governed by the provincial governments.…”
Section: Introductionmentioning
confidence: 99%